Pemahaman Mendalam Terhadap Warisan Budaya Lokal dalam Dinamika Modernisasi - Gunarti, Tri Tami; Hasan, Muhammad Nur (Proceedings of Annual Conference for Muslim Scholars, 2024)
The tradition of tilik, a form of social visit among community members, is a local cultural heritage still preserved by the people of Solokuro District, Lamongan. This tradition plays a vital role in strengthening social bonds and upholding communal values. However, with the rapid pace of modernization bringing about social and technological changes, the tilik tradition faces the challenge of sustainability. This research aims to understand how the tilik tradition adapts in the context of modernization and to identify the factors influencing the changes or continuity of this tradition. Using a phenomenological approach, this study explores the experiences and perspectives of local people regarding the meaning and relevance of the tilik tradition in their daily lives. The results show that although modernization has changed some social aspects, the tilik tradition remains a vital form of social interaction, albeit with adjustments in its implementation. This research is expected to provide deeper insights into the importance of maintaining a balance between preserving local culture and the need for adaptation in the modern era.